Single-step electrospun TiO2–Au hybrid electrodes for high selectivity photoelectrocatalytic glutathione bioanalysis - Anitha Devadoss (Journal of Materials Chemistry B, 2016)
Understanding the fundamentals of photoelectrocatalytic (PEC) biomolecular oxidation benefits thedevelopment of next-generation PEC biosensors. In this work, single-step electrospun titanium-di-oxide–gold (TiO2–Au) hybrid nanofibers (HNF) are reported as being a potential candidate for PEC glutathione(GSH) bioanalysis. The chemical environment of TiO2 and TiO2–Au HNFs were studied with X-ray photoelectronspectroscopy and found to have a strong electronic interaction between TiO2 and the Au nanoparticles(NPs). The PEC measurements revealed that the intramolecular backbone hydrogen bonding ofGSH molecules predominantly contributes highly active Au–GSH bio-nano interfaces, which facilitate thePEC oxidation rate of GSH and thus enhance the photocurrent. Furthermore, the Au NPs present act asauxiliary electron transport channels resulting in enhanced charge collection at the external circuit. As aresult, the TiO2–Au electrode generated a two-fold higher photocurrent density of B84.4 mA cm2 in thepresence of 0.5 mM GSH, where the pristine TiO2 NFs displayed only a negligible influence. Likewise, theTiO2–Au HNF electrode showed a higher sensitivity of 0.002 mM and a wide linear detection rangebetween 0.022 mM and 0.7 mM, with a superior selectivity towards GSH bioanalysis over ascorbic acidand glucose at 0.33 V (versus silver/silver chloride) than that obtained with pristine TiO2. The implicationsof these findings towards the development of a next-generation PEC biosensor are discussed.